A randomized controlled trial comparing sleep hygiene advice with a self-help book focusing on cognitive behavioral therapy for insomnia: a study among patients with prescribed hypnotics from the GP - Bjørn Bjorvatn; Ragnhild Stokke Lundetræ; Øystein Vedaa; Ståle Pallesen; Linn Nyjordet Evanger (Scandinavian Journal of Primary Health Care)
Background Chronic insomnia is commonly treated with hypnotics. However, the treatment of choice is cognitive behavioral therapy for insomnia (CBTi). We investigated whether a self-help book based on CBTi is effective in reducing hypnotic use and improving sleep.Methods Patients who had received a prescription from their GP for z-hypnotics (zopiclone or zolpidem) in the last 6 months were recruited through PraksisNett, an infrastructure within General Practice, for a randomized controlled trial comparing written materials in form of a sheet of sleep hygiene advice and a self-help book. The participants completed an online questionnaire about hypnotic use, insomnia symptoms, sleep duration, anxiety and depression before the intervention and at 4-5 months follow-up.Results In total, 125 patients (response rate 72.7%) completed the follow-up questionnaire. Interaction analyses indicated effects favoring the self-help book for hypnotic use and anxiety. The book reduced the proportion using hypnotics daily from 25.4% to 18.6%, while the proportion increased from 21.2% to 22.7% in the sleep hygiene group. The proportion reporting anxiety was reduced from 32.1% to 23.2% in the self-help book group, while it increased from 27.0% to 31.7% in the sleep hygiene group. Insomnia symptoms were lowered in both intervention groups, whereas depression remained unchanged.Conclusion This study indicated that the self-help book was an effective low-threshold treatment option that seems to reduce hypnotic use and at the same time improve sleep and mental health. The patients who received sleep hygiene advice also reported some positive effects, but daily hypnotic use and anxiety increased.